Decision regret in breast cancer patients after adjuvant radiotherapy - Köksal, Mümtaz; Hoppe, Clara; Schröder, Anna-Katharina; Scafa, Davide; Koch, David; Sarria, Gustavo R.; Leitzen, Christina; Abramian, Alina; Kaiser, Christina; Faridi, Andree; Henkenberens, Christoph; Schmeel, Leonard C.; et al. (The breast, 2023)
Purpose - Breast cancer patients often engage in shared decision-making to select an individualized treatment regimen from multiple options. However, dissatisfaction with treatment outcomes can lead to decision regret. We evaluated decision regret and physical and psychological well-being among breast cancer patients who underwent adjuvant radiotherapy and explored their associations with patient, tumor, treatment, and symptom characteristics. - Methods - This cross-sectional study involved retrospectively obtaining clinical data and data collected through interviews carried out as part of regular long-term medical aftercare. Decision regret regarding the radiotherapy was assessed using the Ottawa Decision Regret Scale, physical and psychological well-being were assessed using the PROMIS Global Health-10 questionnaire, and patients were asked about their treatment outcomes and symptoms. The questionnaire was administered 14 months to 4 years after completion of radiotherapy. - Results - Of the 172 included breast cancer patients, only 13.9% expressed high decision regret, with most patients expressing little or no decision regret. More decision regret was associated with volumetric modulated arc therapy, chest wall irradiation, use of docetaxel as a chemotherapy agent, lymphangiosis carcinomatosa, new heart disease after radiotherapy, and lower psychological well-being. - Conclusion - Although most patients reported little or no decision regret, we identified several patient, treatment, and symptom characteristics associated with more decision regret. Our findings suggest that psychological well-being influences patients’ satisfaction with therapy decisions, implying that practitioners should pay special attention to maintaining psychological well-being during shared decision-making and ensuring that psychological assessment and treatment is provided after cancer therapy to deal with long-term effects of radiotherapy.